2020
DOI: 10.18632/oncotarget.27546
|View full text |Cite
|
Sign up to set email alerts
|

Entinostat augments NK cell functions via epigenetic upregulation of IFIT1-STING-STAT4 pathway

Abstract: Histone deacetylase inhibitors (HDACi) are an emerging cancer therapy; however, their effect on natural killer (NK) cell-mediated anti-tumor responses remain unknown. Here, we evaluated the impact of a benzamide HDACi, entinostat, on human primary NK cells as well as tumor cell lines. Entinostat significantly upregulated the expression of NKG2D, an essential NK cell activating receptor. Independently, entinostat augmented the expression of ULBP1, HLA, and MICA/B on both rhabdomyosarcoma and Ewing sarcoma cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 67 publications
2
24
0
Order By: Relevance
“…HDACi may also impact directly on NK cells, for example, via up-regulation of NKG2D and stimulation of IFNg release and toxicity in NK-tumor cell co-cultures [ 32 ]. However, HDACi monotherapy was already tested in clinical trials but received rather disappointing results [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…HDACi may also impact directly on NK cells, for example, via up-regulation of NKG2D and stimulation of IFNg release and toxicity in NK-tumor cell co-cultures [ 32 ]. However, HDACi monotherapy was already tested in clinical trials but received rather disappointing results [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the killing function of NK cells was also enhanced. In terms of its mechanism, entinostat increases the accessibility of the chromatin in the promoter region of interferon-induced protein with tetratripeptide repeats 1 (IFIT1), thus upregulating the mRNA and protein expression levels of IFIT1 and enhancing the IFIT1–STING–STAT4 pathways mediated by IFIT1 ( 52 ). However, further studies investigating whether HDACi also promotes the killing function of NK cells by regulating acetylation, thereby eliminating recipient APCs and inhibiting GVHD, are warranted.…”
Section: Effects Of Hdacis On Gvhdmentioning
confidence: 99%
“…Further, entinostat downregulates c-FLIP expression concomitantly redirecting Fas cellular localization to the lipid rafts, sensitizing sarcoma cells to FasL-mediated apoptosis [ 129 , 196 ]. Other groups have shown that entinostat increases the expression of MICA/B, ULBP1/2/5/6, and CD155 in OS, RMS, and EWS cells, enhancing NK cell cytotoxicity [ 197 , 198 ]. However, in a nude mice OS lung metastases model, no significant effects of the treatment were observed.…”
Section: Nk Cell-based Therapies In Sarcomasmentioning
confidence: 99%
“…The lack of efficacy was linked with the failure of NK cells to penetrate inside the tumor nodules [ 197 ]. Besides, although preliminary studies report entinostat-mediated enhancement of NK cell effector function, both HDAC inhibition and DNA hypomethylation have been linked to NK cell cytotoxicity impairment, raising caution against combining them with NK cell-based therapies [ 198 , 199 , 200 ].…”
Section: Nk Cell-based Therapies In Sarcomasmentioning
confidence: 99%